The Café Manymak Project - Young, Maggie (The Australian Journal of Indigenous Education, 2000)
The day my class of 10 to 12 year-olds transformed a classroom into a café complete with red gingham tablecloths, travel posters and cooking equipment was the beginning of an exciting, engrossing and most rewarding learning experience.